The fiery trial : Abraham Lincoln and American slavery - Foner, Eric, 1943- (New York : W. W. Norton & Co., 2010)
In a landmark work of deep scholarship and insight, Foner gives us a life of Lincoln as it intertwined with slavery, the defining issue of the time and the tragic hallmark of American history. The author demonstrates how Lincoln navigated a dynamic political landscape deftly, moving in measured steps, often on a path forged by abolitionists and radicals in his party, and that Lincoln's greatness lay in his capacity for moral and political growth.
"I am naturally anti-slavery" : young Abraham Lincoln and slavery -- "Always a Whig" : Lincoln, the law, and the second party system -- "The monstrous injustice" : becoming a republican -- "A house divided" : slavery and race in the late 1850s -- "The only substantial difference" : secession and Civil War -- "I must have Kentucky" : the border strategy -- "Forever free" : the coming of emancipation -- "A new birth of freedom" : securing emancipation -- "A fitting, and necessary conclusion" : abolition, reelection, and the challenge of reconstruction -- Epilogue : "Every drop of blood" : the meaning of the war.
Includes chronology of Lincoln, slavery, and emancipation (p. 339-345) and bibliographical references (p. 349-406) and index.
Pulitzer Prize for history, 2011
Keywords: Lincoln, Abraham, -- 1809-1865 -- Views on slavery; Enslaved persons -- Emancipation -- United States